PEMAHAMAN LITERASI MEDIA DI LINGKUNGAN PENGURUS PIMPINAN WILAYAH AISYIYAH DAERAH ISTIMEWA YOGYAKARTA PERIODE 2015-2020 - Ulfah, Mariana; Fajri, Choirul; Fadillah, Dani (Universitas Negeri Yogyakarta, 2017)
As parents mothers play an important role in giving directions to targeted all relating to the event who deserves to consume by family. This study was conducted by adopting descriptive quantitative. Handing out the questionnaire to the Leader of